2022
DOI: 10.3390/su14138024
|View full text |Cite
|
Sign up to set email alerts
|

Metal Contents and Pollution Indices Assessment of Surface Water, Soil, and Sediment from the Arieș River Basin Mining Area, Romania

Abstract: The current study was conducted to assess the level and spatial distribution of metal pollution in surface water, soil, and sediment samples from the Arieș River basin, located in central Romania, an area impacted by various mining and industrial operations. Several pollution indices, spatial distributions, cluster analyses, principal component analyses, and heat maps were applied for evaluating the contamination level with Ni, Cu, Zn, Cd, Pb, Mn, As, and Hg in the area. Based on the results of the Heavy-Metal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 69 publications
2
17
0
2
Order By: Relevance
“…HM Content Evaluation in Soil ExtractsSimulation of HM concentrations by indices can show how HM accumulation in soils and water can impair plant, human, and animal health (Asmoay, 2017, Asmoay et al, 2019; Zhang et al, 2022). P sum levels differed between 0.43 and 4.43 (Table 1 & Fig.6), which stated that the HM concentrations in the soil extracts had no harmful impact on health(Hakanson, 1980;Hooda, 2010;Gao et al, 2013); Ming, 2014;Moldovan et al, 2022). RI values varied from 2.02 to 9.66 (Table1and Fig.7), showing a minimal ecological risk associated with the concentrations of HM in soil extracts(Hakanson, 1980;Hooda, 2010;Yan et al, 2022).…”
mentioning
confidence: 94%
“…HM Content Evaluation in Soil ExtractsSimulation of HM concentrations by indices can show how HM accumulation in soils and water can impair plant, human, and animal health (Asmoay, 2017, Asmoay et al, 2019; Zhang et al, 2022). P sum levels differed between 0.43 and 4.43 (Table 1 & Fig.6), which stated that the HM concentrations in the soil extracts had no harmful impact on health(Hakanson, 1980;Hooda, 2010;Gao et al, 2013); Ming, 2014;Moldovan et al, 2022). RI values varied from 2.02 to 9.66 (Table1and Fig.7), showing a minimal ecological risk associated with the concentrations of HM in soil extracts(Hakanson, 1980;Hooda, 2010;Yan et al, 2022).…”
mentioning
confidence: 94%
“…Extremely high concentrations were also observed in other river sediments from different mining sites around the globe (Table 3). In a recent study, Moldovan et al [53] reported the concentrations of toxic elements in stream sediments of the Aries , River, Romania. Although this river drains an important area where intensive mining activities took place since Roman times, the concentrations were very low (Table 3).…”
Section: Sources Of Sediment Contaminationmentioning
confidence: 99%
“…It is defined as the concentration of metal in the sample divided by the concentration of metal in the background system. It is expressed mathematically in equation ( 8) (Feher et al 2016;Moldovan et al 2022)…”
Section: Contamination Factormentioning
confidence: 99%